Draft framework for protocol development for EFSA's scientific assessments. Issue 4 (27th April 2020) - ,; Martino, Laura; Aiassa, Elisa; Halldórsson, ÞórhallurIngi; Koutsoumanis, Konstantinos Panagiotis; Naegeli, Hanspeter; Baert, Katleen; Baldinelli, Francesca; Devos, Yann; Lodi, Federica; Lostia, Alfonso; Manini, Paola; et al.
Abstract : During 2014‐2018, EFSA defined a series of principles for the scientific assessment process (impartiality, methodological rigour, transparency and engagement) and developed a 4‐stepapproach (plan/do/verify/report)to facilitate their fulfilment. According to the approach, the methods for the scientific assessmentmust be planned upfront in aprotocol to prevent data‐driven decisions and to increase rigour and transparency of the process.Following the decision to gradually implement the 4‐step approach in all EFSA's non‐application scientific assessments, it was deemed necessary to set up recommendations for protocol development. This technical report provides these recommendations. The document is published as a draftbecause the framework for protocol development will be tested in EFSA's non‐application assessmentsover a one‐yearperiod and revised accordingly.